Ernest's special Christmas. - Barnes, Laura T. (Sergeantsville, N.J. : Barnesyard Books, 2003)
As Ernest and his friends begin to prepare to celebrate Christmas, they realize one of them is missing and discover the most special Christmas gift of all.
K-3
Keywords: Animals - Fiction; Christmas - Fiction; Interpersonal relations - Fiction